OPTIMASI PENAMBAHAN KONSENTRASI UREA DALAM SUBSTRAT PADA PRODUKSI DAN SIFAT ORGANOLEPTIK NATA DARI AIR LEGEN - K. Ni'mah; Ngadiani Ngadiani (STIGMA: Jurnal Matematika dan Ilmu Pengetahuan Alam Unipa, 2013)
The aim of this study to find optimum concentration of urea in production, firmness and sensory properties of nata. This study was conducted using a completely randomized experimental design consisting 4 levels concentrations of urea (3, 4, 5 and 6 g/ l) with 6 replication. Fermentation processes were conducted using Acetobacter xylinum in room temperature (27oC) under light condition for 10 days. The results showed that the urea concentration in substrate medium significantly (P<0.05) effect on production and firmness nata. Highest production (503.5±72,5 g/l) and firmness (32.25±1.48 mm/s) of nata have obtained from 4 g/l urea in medium. Neverless, panelist most prepered color of nata from 6 g/l urea. Meanwhile panelists most prepared taste and smell of nata from 4 g/l. Key words: urea, water legen, Nata, Acetobacter xylinum, production, firmness, organoleptic